2009
DOI: 10.4028/www.scientific.net/kem.417-418.317
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hot Spots Evolution on Brake Disc Using High-Speed Infrared Camera

Abstract: The hot spot generation has been considered as the main degradation mechanism in railway brake disc. Therefore, the understanding of hot spots, also called hot judder, which is undesirable low frequency vibrations developed by non-uniform contact area between brake pad material and brake disc, is important for a better understanding of material design as well as enhancement of materials properties in railway brake disc. Also, infrared (IR) thermography is a powerful NDE technique for the characterization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In this study, two types of railway materials were used: axle railway steel for diesel electric locomotives and glass fiber-reinforced epoxy polymer matrix composites (PMCs) for railway bogies. In the case of railway steel materials, the tensile specimens for this study were prepared by machining on the axle of a diesel electric locomotive [6,7], and dog-bone flat specimens were prepared from the actual axle. For PMC samples, the actual tensile specimens were obtained from E-glass fiber-reinforced epoxy composites.…”
Section: Tensile Testing Interpretation Of Railway Materials Using Irmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, two types of railway materials were used: axle railway steel for diesel electric locomotives and glass fiber-reinforced epoxy polymer matrix composites (PMCs) for railway bogies. In the case of railway steel materials, the tensile specimens for this study were prepared by machining on the axle of a diesel electric locomotive [6,7], and dog-bone flat specimens were prepared from the actual axle. For PMC samples, the actual tensile specimens were obtained from E-glass fiber-reinforced epoxy composites.…”
Section: Tensile Testing Interpretation Of Railway Materials Using Irmentioning
confidence: 99%
“…The initial braking speed (km/h) and the sequence of braking tests were as follows: 65,35,95,65,110,95,95,35,110,65,65,95,110,110,35,35, and 65 km/h. Braking tests for this study were performed using a full-scale dynamometer operated at the Korea Railroad Research Institute (KRRI) [6,11,12].…”
Section: Brake Disc Surface Monitoring During Braking Using Dynamometermentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works on the tribology of friction pairs have been presented, including the study [26]. The authors of [10] showed the results of tests obtained on actual objects of the rail vehicle braking system, showing the phenomenon of generating hot areas during the tribological tests of friction pairs of rail brakes. Such phenomena reduce the braking effectiveness and cause chemical changes in the structure of brake elements made of organic materials.…”
mentioning
confidence: 99%